Innovation investment and its impact on permanent employment - Velez Osorio, Iris Maria (Business: Theory and Practice, 2023)
Through investment in scientific, technological, and innovation activities and investment in computer equipment and communication, organizations try to create a strategy that helps them establish a better innovation performance. Mainly when these organizations are from the manufacturing industry, but the real challenge is how to connect these investments with a political of permanent employment that allows creating a good environment to create and innovate with employees willing to give their experience and knowledge to develop the best products and services. In this analysis, the relationship between investment in scientific, technological, and innovation activities, computer equipment and communications, and hiring permanent human resources are tested, with a sample of 6284 companies in 33 subsectors, a multivariate analysis using regression method and SPSS software was carried out. This paper contributes to the resources and dynamic capability view, describing how investment in innovation can help create permanent human resources that improve the innovation cycle and develop capabilities in human resources to improve innovation performance. Implications for industries and management policy are described, and possible future studies on this subject.